(untitled) (Tikrit Journal of Pharmaceutical Sciences, 2023)
Background: hydatid cyst remains an important public health problem in endemic area. The liver is the organ most frequently infested by hyclatid disease and medical therapy alone is ineffective in eliminating the parasite. The surgical treatment technique for liver hydatid cyst can not be standardized, and the surgical technique should be tailored according co the extent of the cyst and any adjunct complications of hydatid disease. Objectives of the surgical intervention is evacuation ·and obliteration of the cystic caviry. Recurrent hydatid cyst is defined as a new growth of an echinococcal cyst after complete surgical removal of the primary one and irrespective to the surgical technique. Material and methods: A prospective study was including (90) patients who were surgically treated for hepatic hydatid cysts, during the period March 2005 to October 2009 in Baghdad and Tiksit Teaching Hospital. 49 patients (54%) were female and the remaining 41 patients (46%) were male. This gives female: males ratio of l.2: I. The surgical procedures were performed for all patients were endocystectomy ± omentoplasty or open peritoneal drainage or capitonnage; that’s compared with regard of early and late postoperative complications and hydatid disease recurrence. The follow up was made in early and late postoperative period by abclom inal ultrasound up to 2 years (6 montbly intervals). Conclusion: abdominal ultrasound is useful easy tech.nique in postoperative fo[low-up. Bndocystectomy +Omentoplasty procedure had not comp I icated by recurrence. Prevention and control remain the best weapons lo eliminate hydati.dosis.